KEARIFAN EKOLOGIS DALAM TOPONIMI DESA DI KECAMATAN SEI KEPAYANG BARAT KABUPATEN ASAHAN - Andini; Muharrina Harahap (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This research aims to identify and describe the categorization of village names and ecological wisdom in the toponymy of villages in Sei Kepayang Barat Kabupaten Asahan. This study uses the theory of toponymic aspects by Sudaryat and the theory of ecological wisdom. The research employs a qualitative descriptive method with data collection techniques including observation, interviews, listening and note-taking, and recording. The findings of this research are as follows: 1) The village names in Sei Kepayang Barat Kabupaten Asahan can be categorized based on the aspects of manifestation and culture; 2) Based on the aspect of manifestation, these village names can be divided into two categories, namely water-based (hydrological) and natural environment backgrounds, especially plants. Villages with names originating from a water-based background include Sei Lendir Village. Meanwhile, villages whose names originate from both water-based and natural environment backgrounds include Sei Jawi-Jawi, Sei Kepayang Kiri, Sei Nangka, Sei Serindan, and Sei Tualang Pandau Villages; 3) Based on the cultural aspect, the village names in Sei Kepayang Barat can be divided into two categories, namely based on the language used and myths or legends. Based on the language used, these village names originate from the Malay and Indonesian languages. Meanwhile, village names linked to myths or legends include Sei Lendir and Sei Serindan Villages; and 4) The embodiment of ecological wisdom in the toponymy of villages in Sei Kepayang Barat is the application of the principle of respect for nature. Keywords: Ecological wisdom; toponymy; Kecamatan Sei Kepayang Barat Kabupaten Asahan